2019
DOI: 10.1088/1367-2630/ab0431
|View full text |Cite
|
Sign up to set email alerts
|

Transmission spectroscopy of a single atom in the presence of tensor light shifts

Abstract: We investigate the interplay between Zeeman and light shifts in the transmission spectrum of an optically trapped, spin-polarized Rubidium atom. The spectral shape of the transmission changes from multiple, broad resonances to a single, narrow Lorentzian with a high resonant extinction value when we increase the magnetic field strength and lower the depth of the dipole trap. We present an experimental configuration well-suited for quantum information applications that enables not only efficient light-atom coup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Our experiment starts with a single 87 Rb atom trapped in a red-detuned far off-resonant dipole trap (FORT) that is loaded from a magneto-optical trap (MOT). This dipole trap is formed by a linearly polarized Gaussian laser beam (wavelength 851 nm) that is tightly focused by a pair of high numerical aperture lenses (NA = 0.75, focal length f = 5.95 mm) to a waist of w 0 = 1.4 µm [11,20]. Part of the atomic fluorescence is collected through the same lenses and coupled into single mode fibers that are connected to avalanche photodetectors (APD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experiment starts with a single 87 Rb atom trapped in a red-detuned far off-resonant dipole trap (FORT) that is loaded from a magneto-optical trap (MOT). This dipole trap is formed by a linearly polarized Gaussian laser beam (wavelength 851 nm) that is tightly focused by a pair of high numerical aperture lenses (NA = 0.75, focal length f = 5.95 mm) to a waist of w 0 = 1.4 µm [11,20]. Part of the atomic fluorescence is collected through the same lenses and coupled into single mode fibers that are connected to avalanche photodetectors (APD).…”
Section: Methodsmentioning
confidence: 99%
“…In comparison to other qubit configurations for neutral atoms, our interface based on the stretched states is more susceptible to noise such as magnetic field fluctuations. In earlier experiments, we have shown that a linearly polarized dipole trap can significantly reduce atomic motioninduced qubit dephasing without impacting the lightatom coupling [11]. One approach to further suppress decoherence is to apply dynamical decoupling (DD) techniques [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%